2016
DOI: 10.1007/s13239-016-0284-8
|View full text |Cite
|
Sign up to set email alerts
|

Pledget-Armed Sutures Affect the Haemodynamic Performance of Biologic Aortic Valve Substitutes: A Preliminary Experimental and Computational Study

Abstract: Surgical aortic valve replacement is the most common procedure of choice for the treatment of severe aortic stenosis. Bioprosthetic valves are traditionally sewed-in the aortic root by means of pledget-armed sutures during open-heart surgery. Recently, novel bioprostheses which include a stent-based anchoring system have been introduced to allow rapid implantation, therefore reducing the duration and invasiveness of the intervention. Different effects on the hemodynamics were clinically reported associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…As previously reported, we are in favour of direct arterial cannulation also in minimally invasive cases to reduce groin complications (10). The subvalvular stent fixation and the absence of any pledget material might reshape the outflow tract and improve transvalvular hemodynamics, with superior gradients and reduced turbulent flow (11), in comparison to the conventional valve of the same manufacturer (1,12). Fallon and colleagues (13) demonstrated the occurrence of PPM in up to 65% of patients documented in the STS database requiring an isolated AVR, with survival rates being significantly reduced for any degree of PPM (moderate to none: HR, 1.08; 95% CI, 1.05 to 1.12; severe to none: HR, 1.32; 95% CI, 1.25 to 1.39), and 10-year adjusted survival rates of 46%, 43%, and 35% for none, moderate, and severe PPM, respectively (P<0.001).…”
Section: Discussionmentioning
confidence: 70%
“…As previously reported, we are in favour of direct arterial cannulation also in minimally invasive cases to reduce groin complications (10). The subvalvular stent fixation and the absence of any pledget material might reshape the outflow tract and improve transvalvular hemodynamics, with superior gradients and reduced turbulent flow (11), in comparison to the conventional valve of the same manufacturer (1,12). Fallon and colleagues (13) demonstrated the occurrence of PPM in up to 65% of patients documented in the STS database requiring an isolated AVR, with survival rates being significantly reduced for any degree of PPM (moderate to none: HR, 1.08; 95% CI, 1.05 to 1.12; severe to none: HR, 1.32; 95% CI, 1.25 to 1.39), and 10-year adjusted survival rates of 46%, 43%, and 35% for none, moderate, and severe PPM, respectively (P<0.001).…”
Section: Discussionmentioning
confidence: 70%
“…We previously reported that transvalvular gradients are reduced in this rapid-deployment valve compared to the conventional valve of the same manufacturer [8, 25]. The subvalvular stent-based fixation system may be the reason for a reduced transvalvular gradient as it reshapes the left ventricular outflow tract, avoids pledgets and reduces turbulent flow [26]. Furthermore, this valve system does not allow the use of a smaller valve size than indicated, which might occur in conventional valves, as undersizing may lead to paravalvular leakage.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid deployment and sutureless aortic valves have the ability to facilitate minimally invasive surgery and are therefore an excellent adjunct to support the required changes in surgical practice [ 2 , 22 , 23 ]. We were able to show improved laminar flow for the Edwards Intuity valve, which opens the left ventricular outflow tract with the stent part of the valve [ 24 ]. This reduces transvalvular gradients and may be a relevant factor contributing to the excellent long-term survival in this patient population [ 3 , 23 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%